2006
DOI: 10.1038/nature04895
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Id2 by the anaphase-promoting complex couples cell cycle exit and axonal growth

Abstract: In the developing nervous system, Id2 (inhibitor of DNA binding 2, also known as inhibitor of differentiation 2) enhances cell proliferation, promotes tumour progression and inhibits the activity of neurogenic basic helix-loop-helix (bHLH) transcription factors. The anaphase promoting complex/cyclosome and its activator Cdh1 (APC/C(Cdh1)) restrains axonal growth but the targets of APC/C(Cdh1) in neurons are unknown. Id2 and other members of the Id family are very unstable proteins that are eliminated as cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
265
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(287 citation statements)
references
References 25 publications
9
265
3
Order By: Relevance
“…In a different experimental system, glucocorticoid-induced decline in proliferation of neural stem cells was abrogated in the presence of 0.5 mM of a potent proteasomal inhibitor MG132, reflecting an involvement of the ubiquitin proteasomal pathway (Sundberg et al, 2006). Furthermore, Id2 has been identified as a potential substrate for some E3 ubiquitin ligase complexes and, thus, can be targeted for proteasomal degradation (Lasorella et al, 2006). Therefore, we investigated whether MG132 would be able to counteract the antiproliferative action of atRA in HaCaT cells.…”
Section: Resultsmentioning
confidence: 99%
“…In a different experimental system, glucocorticoid-induced decline in proliferation of neural stem cells was abrogated in the presence of 0.5 mM of a potent proteasomal inhibitor MG132, reflecting an involvement of the ubiquitin proteasomal pathway (Sundberg et al, 2006). Furthermore, Id2 has been identified as a potential substrate for some E3 ubiquitin ligase complexes and, thus, can be targeted for proteasomal degradation (Lasorella et al, 2006). Therefore, we investigated whether MG132 would be able to counteract the antiproliferative action of atRA in HaCaT cells.…”
Section: Resultsmentioning
confidence: 99%
“…Stability of all ID proteins appears to be regulated by the ubiquitin proteasome system (Anand et al, 1997;Bounpheng et al, 1999;Fajerman et al, 2004;Lasorella et al, 2006). Indeed, ID proteins can bind different components of , 1997), and ID1 and ID3 bind to the JAB1 protein, a subunit of the COP9 signalosome (Bounpheng et al, 1999;Berse et al, 2004;Trausch-Azar et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This phosphorylation event may trigger their ubiquitin-mediated proteasomal degradation and/or alter their protein-binding specificities (Deed et al, 1997;Bounpheng et al, 1999). All ID proteins but ID3 contain a destruction box (D box), a recognition sequence for the anaphase-promoting complex (APC/ C) (Lasorella et al, 2006), targeting them for ubiquitinmediated proteasomal degradation. In addition, ID1 can interact with the 26S proteasome subunit S5A/ Rpn10 (Anand et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Degradation of Six1 by the APC is notable, as currently only two other transcription factors, HOXC10 (Gabellini et al, 2003) and Id2 (Lasorella et al, 2006), have been identified as APC targets. Like Six1, Id2 is a developmentally important transcription factor that affects cellular proliferation and tumor progression (Lasorella et al, 2001).…”
Section: Discussionmentioning
confidence: 99%